Vitamin D Deficiency in Athletes: A Narrative Review of Injury Risk, Recovery, Immune Function, and Physical Performance - Kwitowska, Patrycja; Ubysz, Eryk; Muraszewski, Łukasz; Muraszewska, Emilia; Lewandowska, Edyta; Król, Agata; Pyjecka, Małgorzata; Paczkowski, Maciej; Łuczyński, Cezary; Wręczycki, Mariusz (Quality in Sport, 2026)
Background. Vitamin D plays a key role in musculoskeletal health, immune function, and recovery. In athletes, vitamin D deficiency is relatively common and has been associated with an increased risk of injury, impaired post-exercise recovery, and reduced physical performance. Aim. To summarize current evidence on the prevalence of vitamin D deficiency in athletes and its associations with injury risk, recovery, immune function, and physical performance. Material and methods. A narrative review of studies published within the last 10 years was conducted to evaluate the prevalence and risk factors of vitamin D deficiency in athletes and its associations with injury risk, recovery, immune function, and physical performance. Results. Available evidence indicates that vitamin D deficiency is relatively common in athletes, particularly in those with limited sun exposure. The most consistent findings concern its association with impaired bone health and increased risk of bone stress injuries. Deficiency may also be related to impaired recovery and altered immune function, while evidence regarding its effect on physical performance remains inconclusive. Conclusions. Vitamin D deficiency may represent an important and modifiable factor related to musculoskeletal health, injury risk, recovery, and physical performance in athletes. Monitoring vitamin D status and individualized supplementation may support athlete health and training outcomes.